Postoperative pulmonary complications in acute type A aortic dissection - Pengfei Chen; Haochao Li; Chenyu Liu; Mingjian Chen; Diming Zhao; Liang Chen; Xiangyang Qian; Jundong Pu; Zujun Chen; Yuetang Wang; Liqing Wang (BMC Surgery)
Abstract Objective The objective of this study was to identify the perioperative risk factors associated with postoperative pulmonary complications (PPCs) following emergency surgery for Acute Type A Aortic Dissection (ATAAD) and to evaluate the impact of these complications on short- and long-term patient outcomes. Methods A retrospective observational analysis was conducted on 750 adult patients who underwent emergency surgery for ATAAD between January 2017 and December 2019. Results The overall in-hospital mortality was 5.7%. Among 750 patients, 91 patients(12.1%) developed PPCs. Multivariable logistic regression analysis indicated that smoking(OR = 2.212, 95%CI: 1.361–3.595, P = 0.001), previous cardiac surgery(OR = 2.818, 95%CI: 1.259–6.310, P = 0.012), CPB time(OR = 1.003, 95%CI: 1.000–1.006, P = 0.047), and red blood cell transfusion(OR = 1.091, 95%CI: 1.059–1.124, P < 0.001) were associated with an increased risk of developing PPCs. Patients who developed PPCs had a higher 30-day mortality rate (P < 0.001), longer lengths of stay in the ICU and hospital(P < 0.001), increased healthcare costs(P < 0.001), and lower long-term survival rates(P = 0.005). Conclusion The incidence of PPCs is high in patients undergoing cardiac surgery for aortic dissection, adversely affecting their prognosis. This study identified four key risk factors associated with the development of PPCs.